Severe acute respiratory syndrome coronavirus E protein transports calcium ions and activates the NLRP3 inflammasome - Nieto-Torres, Jose Luis; Verdiá-Báguena, Carmina; Jimenez-Guardeño, Jose Manuel; Regla-Nava, Jose Angel; Castaño-Rodriguez, Carlos; Fernandez-Delgado, Raul; Torres, Jaume; Aguilella, Vicente M; Enjuanes, Luis (Elsevier, 2015)
Severe acute respiratory syndrome coronavirus (SARS-CoV) envelope (E) protein is a viroporin involved in virulence. E protein ion channel (IC) activity is specifically correlated with enhanced pulmonary damage, edema accumulation and death. IL-1β driven proinflammation is associated with those pathological signatures, however its link to IC activity remains unknown. In this report, we demonstrate that SARS-CoV E protein forms protein-lipid channels in ERGIC/Golgi membranes that are permeable to calcium ions, a highly relevant feature never reported before. Calcium ions together with pH modulated E protein pore charge and selectivity. Interestingly, E protein IC activity boosted the activation of the NLRP3 inflammasome, leading to IL-1β overproduction. Calcium transport through the E protein IC was the main trigger of this process. These findings strikingly link SARS-CoV E protein IC induced ionic disturbances at the cell level to immunopathological consequences and disease worsening in the infected organism.
Keywords: Virulencia (Microbiología); SARS-CoV; Coronavirus; E protein; Ion channel; Viroporin; Calcium; Inflammasome; Pathogenesis